Serum irisin concentration in women with gestational diabetes. (22nd May 2014) - Kuzmicki, Mariusz; Telejko, Beata; Lipinska, Danuta; Pliszka, Justyna; Szamatowicz, Michal; Wilk, Juliusz; Zbucka-Kretowska, Monika; Laudanski, Piotr; Kretowski, Adam; Gorska, Maria; Szamatowicz, Jacek
Abstract: Irisin is a novel myokine and adipokine which induces an increase in total body energy expenditure, improving insulin sensitivity and glucose tolerance in experimental animals. In the present study, serum irisin concentration was measured by an enzyme immunoassay in 130 women with gestational diabetes mellitus (GDM) and 140 BMI-matched patients with normal glucose tolerance (NGT). Median irisin level was significantly lower in the patients with GDM than in the NGT subjects (1703.3 [1354.8–2097.9 ng/ml] versus 1873.8 [1519.8–2294.8 ng/ml], p  = 0.01); however, 3 months after childbirth its concentrations did not differ markedly between the two groups (1165.9 [872.1–1497.5] ng/ml versus 1139.0 [984.0–1376.7] ng/ml). In the whole group, irisin concentration correlated negatively with 2 h glucose level ( R  = −0.14, p  = 0.03). In the women with NGT, irisin concentration correlated positively with ISOGTT ( R  = 0.22, p  = 0.04) and the disposition index (DI120 ) ( R  = 0.24, p  = 0.03), as well as negatively with 2 h insulin level ( R  = −0.23, p  = 0.03) and HOMA-IR ( R  = −0.24, p  = 0.02). Multiple regression analysis revealed that 2 h glucose and DI120 were the only variables significantly influencing serum irisin ( β  = 0.158, p  = 0.03 and β  = 0.159, p  = 0.02, respectively). Our results suggest that serum irisin concentration increases markedly in pregnant women, but this increase seems to be significantly lower in patients with GDM. Chinese abstract: 鸢尾素是一种新发现的肌细胞因子和脂肪因子，在动物实验中，可以提高全身能量消耗，提高胰岛素敏感性和糖耐量。本研究通过酶免测定法测定了130名妊娠糖尿病(GDM)妇女和140名BMI值相匹配的糖耐量正常(NGT)妇女血清鸢尾素浓度。GDM患者中位血清鸢尾素浓度较NGT妇女明显降低(1703.3 [1354.8–2097.9 ng/ml] 比1873.8 [1519.8–2294.8 ng/ml], p=0.01)；而在分娩三个月后两组妇女血清鸢尾素浓度并无明显差异(1165.9 [872.1–1497.5] ng/ml 比 1139.0 [984.0–1376.7]ng/ml)。所有受试对象的血清鸢尾素浓度均与餐后2h 血糖呈负相关(R=－0.14, p=0.03)。NGT妇女血清鸢尾素浓度与处置指数（DI120 ）(R=0.24, p=0.03)和ISOGTT (R=0.22, p=0.04)正相关，与2h胰岛素水平(R=－0.23, p=0.03)和HOMA-IR (R=﹣0.24, p=0.02)负相关。多元回归分析显示只有餐后2h血糖与DI120 是显著影响血清鸢尾素浓度的变量(分别为β=0.158, p=0.03 和β=0.159, p=0.02)。研究结果显示妊娠妇女血清鸢尾素浓度明显增高，而在GDM妇女这种升高值则明显降低。